Correlation between the Optic Nerve Sheath Diameter Measurement and Intracranial Hypertension Tomographic Findings from a Colombian Hospital - Caballero-Lozada, Andrés Fabricio; Miño-Bernal, Jorge Fernando; Espinosa-Marsiglia, Rene Alberto; Rojas-Rincón, Valentina (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Objective In the present study, we aimed at determining the correlation between tomographic findings of intracranial hypertension and ultrasound measurement of the optic nerve sheath diameter (ONSD).Methods Observational, descriptive, prospective, cross-sectional pilot study. The present research was performed in a tertiary hospital in Cali, Colombia, from March 2019 to October 2019. Twenty-five patients constituted the intracranial hypertension group, and 25 patients without intracranial hypertension constituted the control group. Ultrasound measurements of the ONSD were assessed using a Sonosite Turbo (SonoSite Inc., Bothell, WA, USA) ultrasound. The computed tomography (CT) images obtained from each patient diagnosed with intracranial hypertension were available in the software of the hospital. The primary outcome was the ultrasound measurement of the ONSD.Results The ONSD values of the right eye of the intracranial hypertension group ranged from 5.2 to 7.6 mm, and the ONSD of the left eye ranged from 5.3 to 7.3 mm. The global ONSD values, obtained from the average between the right and left eye, were recorded between 5.25 and 7.45 mm. Overall, our study indicated that ultrasound measurements of the ONSD were effective in differentiating a group with intracranial hypertension, previously diagnosed by CT scan images, from patients without this condition. According to the ROC curve, the optimal cutoff point for detecting intracranial hypertension was 5.2 mm.Conclusions Ultrasound measurements of the ONSD correlated with the measurements obtained from CT scan images, suggesting that the ultrasound technique can be efficient in identifying patients with intracranial hypertension and valuable in cases when CT scan images are not an available option.
Keywords: Optic nerve; Intracranial hypertension; Ultrasonography; Tomography, X-Ray Computed